Measurement of the CP asymmetry in B(0)→K(*0)μ(+)μ(-) decays. - Aaij, R; Abellan Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
A measurement of the CP asymmetry in B(0)→K(*0)μ(+)μ(-) decays is presented, based on 1.0 fb(-1) of pp collision data recorded by the LHCb experiment during 2011. The measurement is performed in six bins of invariant mass squared of the μ(+)μ(-) pair, excluding the J/ψ and ψ(2S) resonance regions. Production and detection asymmetries are removed using the B(0)→J/ψK(*0) decay as a control mode. The integrated CP asymmetry is found to be -0.072±0.040(stat)±0.005(syst), consistent with the standard model.